2020
DOI: 10.1093/ofid/ofaa564
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Direct-Acting Antiviral Therapy in People Actively Using Drugs and Alcohol: The INCLUD Study

Abstract: Background HCV treatment in persons who use drugs (PWUD) is often withheld due to adherence and reinfection concerns. Here, we report treatment outcomes, technology-based adherence data, and adherence predictors in PWUD and/or alcohol. Methods INCLUD was a prospective, open-label study of ledipasvir/sofosbuvir for 12 weeks in PWUD aged 18-70 years. Participants were randomized to wireless (WOT, Wisepill®) or video-based direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Not surprisingly, since patients without history of decompensated liver disease constituted the majority of the study group, similar trend was observed in the overall population analysis. The impact of non‐adherence to the treatment, dose modification or disruption on SVR has been investigated predominantly in people with injection drug use or opioid agonist therapy, for whom SVR rates were high in both nonadherent and adherent populations over a range of adherence values from 30%‐101% 53,54 . On the other hand, it is true that some studies demonstrated little room for "forgiveness" in case of non‐adherence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not surprisingly, since patients without history of decompensated liver disease constituted the majority of the study group, similar trend was observed in the overall population analysis. The impact of non‐adherence to the treatment, dose modification or disruption on SVR has been investigated predominantly in people with injection drug use or opioid agonist therapy, for whom SVR rates were high in both nonadherent and adherent populations over a range of adherence values from 30%‐101% 53,54 . On the other hand, it is true that some studies demonstrated little room for "forgiveness" in case of non‐adherence.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of non-adherence to the treatment, dose modification or disruption on SVR has been investigated predominantly in people with injection drug use or opioid agonist therapy, for whom SVR rates were high in both nonadherent and adherent populations over a range of adherence values from 30%-101%. 53,54 On the other hand, it is true that some studies demonstrated little room for "forgiveness" in case of non-adherence. An analysis of randomized controlled trials reported 96.2% adherence to ledipasvir/sofosbuvir, with an SVR rate of 97.1% in adherent patients (taking > 80% of prescribed doses) and 82.5% in nonadherent patients (P <.0001).…”
Section: Discussionmentioning
confidence: 99%
“…I do not expect miracles after starting my treatment. 18. I strictly respect what the doctor tells me.…”
Section: Questions Of Initial Questionnaire Hcv-ad Reasonsmentioning
confidence: 88%
“…Studies so far have focused on pill counts (PC) [14], the use of Visual Analog Scale (VAS) [15] and mostly pharmacy records [16,17], which help to construct a general idea in specific situations over medication adherence. The number of wireless pillbox openings or video-recorded ingestions was used for DAA adherence monitoring [18]. However, other factors should be considered too, such as previous treatment experience, which may generate medication administration fear, as well as multi-tablet therapy by adding more medication to their previous treated comorbidities [19].…”
Section: Introductionmentioning
confidence: 99%
“…The PWID populations in India show wide variation in socio-demographic characteristics, awareness of HIV and viral hepatitis, social acceptance of therapy and deaddiction services, type of drug use or injection patterns and social stigma [14] . A combined approach, task shifting, decentralized approach with linked services is essential to improve adherence [15] . To this end, the Mukh Mantri Punjab Hepatitis C Relief Fund (MMPHCRF) program provides algorithm-based, free- of-charge generic, all-oral DAAs therapy in the state of Punjab, a model that was replicated across the country under the National Viral Hepatitis Elimination Programme (NVHCP) [4 , 16] .…”
Section: Introductionmentioning
confidence: 99%